2022
DOI: 10.57187/smw.2022.40001
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medicine in Switzerland: an analysis of physician workforce, gender equality and academics

Abstract: BACKGROUND: Globally, emergency medicine is continuously evolving and in numerous countries, societies and colleges help develop the specialty on a professional and academic level. However, there are countries, including Switzerland, where emergency medicine is not a fully recognised specialty and there is a historical gender gap.AIMS OF THE STUDY: It was the aim of this study to investigate the trends and developments in Swiss emergency medicine in terms of physician workforce, gender equality and academic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…39 Since 2009, physicians working in EDs can apply for a certificate in emergency medicine. 40 The certificate of emergency medicine requires 24 months of additional training in addition to a board-certified specialty in internal medicine, surgery, anaesthesiology, intensive care, orthopaedic surgery, traumatology or cardiology and focuses on in-hospital emergency care. Education of physicians working in emergency medicine in Switzerland is regulated through the Swiss Society of Emergency and Rescue Medicine (SSERM).…”
Section: Study Settingmentioning
confidence: 99%
“…39 Since 2009, physicians working in EDs can apply for a certificate in emergency medicine. 40 The certificate of emergency medicine requires 24 months of additional training in addition to a board-certified specialty in internal medicine, surgery, anaesthesiology, intensive care, orthopaedic surgery, traumatology or cardiology and focuses on in-hospital emergency care. Education of physicians working in emergency medicine in Switzerland is regulated through the Swiss Society of Emergency and Rescue Medicine (SSERM).…”
Section: Study Settingmentioning
confidence: 99%
“…The relevant literature confirmed that, although there has been progress for women in medicine (Joseph et al, 2021), the gender gap is still present in healthcare sector and is rooted in gender biases and gender norms that date back thousands of years (Newman et al 2020). In such a direction, several authors shed light on the fact that different fields of medicine, including paediatrics (Spector et al, 2019), emergency medicine (Ravioli et al, 2022), and plastic surgery (Moeller et al, 2021), is not leading the way in gender equity.…”
Section: Gender Equity In Hospitals: Still a Long Way To Gomentioning
confidence: 99%
“…Hypercalcemia could result from osteolytic lesions or from production of humoral substances like parathyroid hormone‐related protein (PTHrP) or uncontrolled synthesis and secretion of 1‐25(OH) 2 D3 by the tumoral cell or macrophages. Within tumor‐related etiologies, multiple myeloma, breast, lung, and kidney cancers are the most frequent 3,4 . In these diseases, hypercalcemia has been reported in 30% and 60% of patients with multiple myeloma and T‐cell non‐Hodgkin lymphoma (NHL) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Within tumor-related etiologies, multiple myeloma, breast, lung, and kidney cancers are the most frequent. 3,4 In these diseases, hypercalcemia has been reported in 30% and 60% of patients with multiple myeloma and T-cell non-Hodgkin lymphoma (NHL). 1 However, hypercalcemia has only been reported in 7%-8% of patients with B-cell NHL and its prevalence and its prognostic value is unclear.…”
Section: Introductionmentioning
confidence: 99%